2015
DOI: 10.1002/jwmg.822
|View full text |Cite
|
Sign up to set email alerts
|

Den entry behavior in Scandinavian brown bears: Implications for preventing human injuries

Abstract: Encounters between Scandinavian brown bears (Ursus arctos) and humans that result in human injuries and fatalities typically coincide with den entry in October and November, and commonly occur near a den. Our aim was to determine when bears arrive at their dens, identify potential predictors of this event, document behavior and activity associated with this period, and attempt to explain the increased risk of bear-caused human injuries in this period. We analyzed global positioning system (GPS) location and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…Sahlén et al. () and Friebe et al. () both reported that older brown bears arrived earlier to their dens.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sahlén et al. () and Friebe et al. () both reported that older brown bears arrived earlier to their dens.…”
Section: Discussionmentioning
confidence: 97%
“…We calculated hibernation start and end dates using activity data from GPS collars (Friebe et al, 2014;Gervasi, Brunberg, & Swenson, 2006;Laske, Garshelis, & Laizzo, 2011;Sahlén, Friebe, Səebø, Swenson, & Støen, 2015). When we successfully determined both dates for a bear over a winter, we also calculated the duration of hibernation.…”
Section: Defining Den Entry and Exit Datesmentioning
confidence: 99%
“…We previously reported that capture of hibernating brown bears resulted in den abandonment in 12 (92%) of 13 captures, compared with 22% overall den abandonment rate in the study area (Sahlén et al ., 2015). Although we do not know of other reports of the effects of capture on denning brown bears, a study reporting the capture of 14 hibernating female American black bears with cubs found that none abandoned their dens (Doan-Crider and Hellgren, 1996); others have reported that capture or approach of black bears during denning resulted in den abandonment rates of 17% (Tietje and Ruff, 1980) and 29% (Goodrich and Berger, 1994).…”
Section: Introductionmentioning
confidence: 88%
“…Although abandoned dens were documented to be more frequently located closer to plowed roads (Elfström and Swenson, 2009), the physical characteristics of the denning site did not differ dramatically between successful and abandoned dens (Elfström et al ., 2008). In Sweden, den abandonment rates are high, with 9% (of 194 bear winters followed by VHF telemetry; Swenson et al ., 1997) and 22% (of 90 followed by the more accurate GPS technology; Sahlén et al ., 2015) changing their dens. Although the later study found no gender differences, pregnant adult females that changed dens had significantly greater cub mortality than those that did not abandon dens (60 vs. 6% lost at least one cub at the den or shortly after leaving it).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation